Using Heidegger's Conceptual Framework to Analyze New Media Technologies and Explain the Effects of Technological Determinism Through the Use of These Media - Sajjadi, Sayed Nabi (Yayasan Lentera Avanya Nagari, 2025)
This paper, drawing upon Martin Heidegger’s conceptual framework, re-examines and philosophically analyzes new media technologies and the implications of “technological determinism.” The research employs a qualitative-hermeneutic phenomenological approach, conducting textual analysis of Heidegger’s primary works and relevant secondary literature. The findings indicate that an instrumental and anthropocentric definition of technology is insufficient; Heidegger views technology not merely as a tool but as a “mode of unconcealment,” particularly as Gestell (enframing), which presents the world as a “standing-reserve” ready for exploitation. The application of this insight to new media yields several key consequences: (1) the pictorial reproduction and “pictorialization” of the cognitive world; (2) the formation of “global time” and the speed of message transmission, which transforms the experience of temporality; (3) the emergence of virtual worlds leading to identity crises and the multiplicity of real/virtual identities; and (4) the reinforcement of deterministic aspects of technology, bearing both positive effects (e.g., networked crisis management) and negative ones (e.g., the colonization of time-identity and reduction of human agency). The discussion argues that a critical engagement with technology necessitates moving beyond a purely instrumental understanding and adopting a stance where humanity is the “master” of technology, not its “slave.” The proposed strategy involves a re-evaluation of “dwelling in unconcealment” and fostering a conscious and reflective approach to media. Finally, the study emphasizes the need for further interdisciplinary research (philosophy of technology, media sociology, and identity psychology) to gain a deeper understanding of the effects of new media.